In-plane ferroelectricity with high Curie temperatures in nonequilibrium SnSe 1-x S x van der Waals semiconductors - Eli Sutter; Peter Sutter (Proceedings of the National Academy of Sciences, 2025)
While symmetry breaking in 2D ferroelectrics is obviously linked to the single-layer structure, layered (van der Waals) ferroelectrics can have a multitude of underlying mechanisms, making their identification nontrivial and often controversial. This complexity is exemplified by tin chalcogenides whose equilibrium structure, the orthorhombic α-phase with space group Pnma , includes an inversion center and which therefore should not be ferroelectric. Yet, recent work demonstrated polarization switching and ferroelectric domains in few-layer SnS and SnSe. Here, we use in situ electron microscopy and diffraction to determine the mechanism and characteristics of ferroelectricity across the SnSe 1-x S x system. We identify two distinct phases of synthetic SnSe 1-x S x : nonpolar (centrosymmetric) equilibrium (α-phase) crystals and metastable crystals adopting a distorted monoclinic structure, which are in-plane ferroelectrics with Curie temperatures of 320 to 420 °C. A surprising structural plasticity of the ferroelectric crystals during heating/cooling indicates a shallow energy landscape. This in turn suggests absence of a pronounced driving force for conversion to the α-phase that can explain the formation of the nonequilibrium crystals and their stability even after transfer to other supports. Our results highlight opportunities for the discovery of novel ferroelectrics among nonequilibrium van der Waals crystals.